ANALYSIS OF REVOCATION OF LAND RIGHTS BY THE GOVERNMENT REVIEWED FROM THE CONCEPT OF LOSS - Natasha Marcella Geovanny; Marchelina Theresia; Devina Felicia Widjaja (Universitas Lampung, 2019)
The control of land by the state is stated in Article 33 paragraph (3) of the 1945 Constitution of the Republic of Indonesia (UUD 1945). Based on this article, it means that the State has authority over land tenure, this encourages the writing of a journal on the application of social functions and the determination of compensation that occurs in the land sector. This research was conducted because the authors see that there are still many disputes related to the implementation of the social function itself and the application of the determination of compensation as stipulated in the provisions relating to this matter it is caused because the application in real life has not been running optimally. This study aims to find out how the government’s authority should be for land tenure and its relation to social functions and the determination of compensation. The location used as a case study is located in Batu Jaya Village, Tangerang City. Data collection is done by interviewing several related parties and also conducting a literature study by finding sources related to government authority over land tenure, the concept of social functions, and the determination of compensation. The results of this study indicate that the government has the power to grant land rights and revoke land rights in the public interest.